Shotgun proteomics of Brassica rapa seed proteins identifies vicilin as a major seed storage protein in the mature seed. - Mahmudur Rahman; Qi Guo; Abdul Baten; Ramil Mauleon; Amina Khatun; Lei Liu; Bronwyn J Barkla (PLoS ONE)
Proteins make up a large percentage of the Brassica seed and are second only to the oil in economic importance with uses for both animal and human nutrition. The most abundant proteins reported in the seeds of Brassica are the seed storage proteins cruciferin and napin, belonging to the 12S globulin and 2S albumin families of proteins, respectively. To gain insight into the Brassica rapa seed proteome and to confirm the presence and relative quantity of proteins encoded by candidate seed storage genes in the mature seed, shotgun proteomics was carried out on protein extracts from seeds of B. rapa inbred line R-o-18. Following liquid chromatography tandem mass spectrometry, a total of 34016 spectra were mapped to 323 proteins, where 233 proteins were identified in 3 out of 4 biological replicates by at least 2 unique peptides. 2S albumin like napin seed storage proteins (SSPs), 11/12S globulin like cruciferin SSPs and 7S globulin like vicilin SSPs were identified in the samples, along with other notable proteins including oil body proteins, namely ten oleosins and two oil body-associated proteins. The identification of vicilin like proteins in the mature B. rapa seed represents the first account of these proteins in the Brassicaceae and analysis indicates high conservation of sequence motifs to other 7S vicilin-like allergenic proteins as well as conservation of major allergenic epitopes in the proteins. This study enriches our existing knowledge on rapeseed seed proteins and provides a robust foundation and rational basis for plant bioengineering of seed storage proteins.